Photophysiological strategies to iron limitation and high light differ between two Antarctic key phytoplankton species - Trimborn, Scarlett; Thoms, Silke; Bischof, Kai; Beszteri, Sara (2019)
As iron (Fe) and light availability strongly influence phytoplankton species distribution in low Fe-waters, we investigated the combined effects of increasing light (20, 200 and 500 μmol photons m−2 s−1) in conjunction with different Fe (0.4 and 2 nM Fe) availability on the physiology of two ecologically relevant phytoplankton species in the Southern Ocean, Chaetoceros debilis (Bacillariophyceae) and Phaeocystis antarctica (Haptophyceae). Combining Fast Repetition Rate fluorometry, elemental composition and pigment analyses with cell-based modelling, new insights on the photophysiological strategies of the two tested species were gained. Fe-deficient cells of P. antarctica displayed similar high growth rates at all irradiances. In comparison, Fe-deplete C. debilis cells grew much slower under low and medium irradiance and were unable to grow at the highest irradiance. Interestingly, Fe-deficient C. debilis cells were better protected against short-term excessive irradiances than P. antarctica. Next to similar electron transfer rates, Fe-deplete C. debilis cells displayed faster re-oxidation of the primary electron acceptor Qa, indicating operation of a putative plastid plastoquinol terminal oxidase, known to create a proton gradient in the thylakoid lumen. In line with this, high xanthophyll activity was shown by its high cellular diadinoxanthin content along with very high NPQ activities. Such strategy was especially efficient after short-term exposure to high irradiance, as seen by the high potential of Fv/Fm recovery (~70-80%), pointing towards a high tolerance of C. debilis to short-term high light stress. This tolerance was, however, counteracted by strongly lowered growth and particulate organic carbon production rates of the diatom relative to the prymnesiophyte. The prymnesiophyte also possessed high photoprotective capabilities, with strong alternative electron cycling activities (electron cycling around photosystem I, Mehler and/or photorespiration) being more important than xanthophyll cycling. ...